EXPECTANCY VIOLATION THEORY (EVT) DALAM FILM ‘DI TIMUR MATAHARI’ (Analisis Peran Vina, Gadis ‘Cina’ Bersuamikan Papua) - agustina, dwi pela (Universitas Teuku Umar, 2018)
Intercultural is the self most effective inter-personal between two people who are of differentcultural backgrounds. The Expectancy Violation Theory (EVT) is a theory that explains thatpeople have expectations about nonverbal behavior of others. Unexpected changes that occurwithin a conversation between communicators can cause a feeling of discomfort or even angerand often ambiguous. Similarly, in the film, the film-makers and actors make the dialogue alongwith the non-verbal language in a movie for menyeampaikan his message to the audience. Inthis case, the authors raised the film